Pengembangan Nilai Moral dan Agama Anak Usia Dini Melalui Kegiatan Festival Anak Saleh - Niarti, Sriyan Kumala; Sundari, Iis; Paramitha, Paramitha; Erni, Erni; Syamsiah, Syamsiah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Objective: This study aims to analyze the effectiveness of the Festival Anak Saleh (FAS) [Pious Children Festival] activities as a means of developing moral and religious values in early childhood. The results indicate that FAS significantly contributes to the instillation of moral and religious values. Through various types of competitions and activities (such as prayer memorization, adhan (call to prayer), and short sermons), children demonstrated improvements in aspects of discipline (punctuality and obedience), responsibility (completing competition tasks), sportsmanship (accepting defeat and victory), and the internalization of religious values (courage to perform and practice worship). Conclusion: The Festival Anak Saleh proves to be an effective and enjoyable platform for practically integrating religious and moral learning, helping to transition these values from abstract concepts into real-life behavior in children's daily lives.